2012
DOI: 10.1620/tjem.226.191
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Regulation Is Disturbed in Children with Euthyroid Hashimoto Thyroiditis

Abstract: Hashimoto thyroiditis (chronic autoimmune thyroiditis) is the most common form of thyroiditis in childhood. Previous studies have found autonomic dysfunction of varying magnitude in patients with autoimmune diseases, which is considered a cardiovascular risk factor. We aimed to evaluate the heart rate variability (HRV), a measure of cardiac autonomic modulation, in children with euthyroid Hashimoto thyroiditis (eHT). The study included 32 patients with eHT (27 girls and 5 boys; mean age 11 ± 4.1 years, range 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Highly variable heart rates are a sign of good autonomic control. [4][5][6] The HRV is assessed by time and frequencydomain variables. There is a general agreement that the high-frequency band (HF) reflects parasympathetic activity and low-frequency band (LF) reflects both parasympathetic and sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly variable heart rates are a sign of good autonomic control. [4][5][6] The HRV is assessed by time and frequencydomain variables. There is a general agreement that the high-frequency band (HF) reflects parasympathetic activity and low-frequency band (LF) reflects both parasympathetic and sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that impaired HRV correlates with an increased risk of cardiovascular mortality. 4,5 It is important to assess the autonomic functions in SLE as some studies proposed that the autonomic fluctuations might predispose to ventricular arrhythmias and circulatory dysfunction. 6,7 Both sympathetic and parasympathetic pathways are associated with acute and chronic inflammation and autonomic dysfunction in SLE.…”
mentioning
confidence: 99%
“…Thyroid disease is a common comorbidity of diabetes and has in itself been reported to lower HRV (Celik et al, 2011; Kilic et al, 2012). This renders it as a possible confounder when studying CAN.…”
Section: Discussionmentioning
confidence: 99%
“…Previously described factors of possible importance for the HRV analysis other than psychosocial stress are as follows: hypoglycemia (Jaiswal et al, 2014; Koivikko et al, 2012), physical activity (Shin et al, 2014), thyroid disease (Kilic, Gulgun, Tascilar, Sari, & Yokusoglu, 2012) and ovulation in fertile women (Weissman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…O aumento da FC antes da realização de uma atividade física é conhecido como "resposta antecipatória da FC" 9,10 . Os mecanismos envolvidos na fisiologia do controle cardiovascular são complexos, e envolvem a interação entre os ramos simpático e parassimpático do sistema nervoso autônomo sobre a autorritimicidade do nódulo sinusal 2,[16][17][18][19][20][21][22][23][24][25] . Parece que, por fatores psicológicos estressantes, decorrentes da atividade a ser realizada, o sistema nervoso autônomo diminui o tônus vagal cardíaco, e aumenta a atividade nervosa simpática, fazendo com que a FC eleve seus valores, mesmo na situação de repouso.…”
Section: Discussionunclassified